German EstSmoke: estimating adult smoking‐related costs and consequences of smoking cessation for Germany. (18th September 2017) - Sonntag, Diana; Gilbody, Simon; Winkler, Volker; Ali, Shehzad
Abstract: Aims: We compared predicted life‐time health‐care costs for current, never and ex‐smokers in Germany under the current set of tobacco control polices. We compared these economic consequences of the current situation with an alternative in which Germany were to implement more comprehensive tobacco control policies consistent with the World Health Organization (WHO) Framework Convention for Tobacco Control (FCTC) guidelines. Design: German EstSmoke, an adapted version of the UK EstSmoke simulation model, applies the Markov modelling approach. Transition probabilities for (re‐)currence of smoking‐related diseases were calculated from large German disease‐specific registries and the German Health Update (GEDA 2010). Estimations of both health‐care costs and effect sizes of smoking cessation policies were taken from recent German studies and discounted at 3.5%/year. Setting: Germany. Participants: German population of prevalent current, never and ex‐smokers in 2009. Measurement: Life‐time cost and outcomes in current, never and ex‐smokers. Findings: If tobacco control policies are not strengthened, the German smoking population will incur €41.56 billion life‐time excess costs compared with never smokers. Implementing tobacco control policies consistent with WHO FCTC guidelines would reduce the difference of life‐time costs between current smokers and ex‐smokers by at least €1.7 billion. Conclusions: Modelling suggests that the life‐time healthcare costs of people in Germany who smoke are substantially greater than those of people who have never smoked. However, more comprehensive tobacco control policies could reduce health‐care expenditures for current smokers by at least 4%.